Public Perception to Covid-19 Outbreak: Study of Mysticism and Spirituality Shalawat Simtu al-Duror - Ahmad Mujib; Abdul Aziz; Muna Yastuti Madrah; Nailil Muna (Jurnal Theologia, 2021)
The Corona Virus pandemic has created policies to foster people to stay healthy and free from this disease. However, there are groups of people who ignored the covid-19 protocol for some mystical and spiritual reasons. This study taking place in Mranggen central java, observing the Majlis shalawat of Jalatunda. The congregation of zikr and prayers of Jalatunda believe that the shalawat of  Simtu al-Durar may avoid them from all kinds of diseases. The value of mysticism strengthens the spirituality of the congregation.  We use a phenomenological approach to describe and explain each variable into material for analysis. This study found that the mysticism exists in public belief has become a vehicle for the practice of reciting shalawat which further improves the spirituality of the congregation of the assembly.